Commentary: Influence of smartphone addiction proneness of young children on problematic behaviors and emotional intelligence: Mediating self-assessment effects of parents using smartphones - TAN, Qin Ying Joanne (Institutional Knowledge at Singapore Management University, 2019)
The majority of studies on smartphone addiction have focused on adults and school-aged children or youth (e.g., Hartanto and Yang, 2016; Chung et al., 2018; Lee et al., 2018); few have investigated the impact of smartphone overuse during infancy and early childhood. Recently, Cho and Lee (2017) surveyed parents of children aged one to six and attempted to address this research gap in their article entitled “Influence of smartphone addiction proneness of young children on problematic behaviors and emotional intelligence: Mediating self-assessment effects of parents using smartphones.” Although the results are interesting, we would caution that they are preliminary because of the study's lack of theoretical grounding and empirical evidence for the proposed mediation model and notable methodological problems. Our primary goal is therefore to draw attention to an alternative conceptual model that elucidates the causal relationship between parents' smartphone use, children's smartphone addiction proneness, and their problematic behaviors. In addition, we discuss methodological issues with sampling methods and psychometric properties of measures and suggest further studies to address these concerns.